2009
DOI: 10.1161/strokeaha.109.557256
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Modified Rankin Scale

Abstract: Background and Purpose-A perceived weakness of the modified Rankin Scale is potential for interobserver variability.We undertook a systematic review of modified Rankin Scale reliability studies. Methods-Two researchers independently reviewed the literature. Crossdisciplinary electronic databases were interrogated using the following key words: Stroke*; Cerebrovasc*; Modified Rankin*; Rankin Scale*; Oxford Handicap*; Observer variation*. Data were extracted according to prespecified criteria with decisions on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(312 citation statements)
references
References 15 publications
9
293
2
8
Order By: Relevance
“…A recent review demonstrated moderate to strong inter-and intraobserver reliability of the mRS, with weighted kappa coefficients of 0.90 and 0.94, respectively. 27 Therefore, individual variations in scoring are unlikely to account for the frequency of delayed improvement found in our study. Additionally, because the number of patients with improved mRS scores at 1 year and 3 years was more than twice the number of patients with worse mRS scores at these same time points, interand intrarater variability is unlikely to account for our findings.…”
Section: Figmentioning
confidence: 70%
“…A recent review demonstrated moderate to strong inter-and intraobserver reliability of the mRS, with weighted kappa coefficients of 0.90 and 0.94, respectively. 27 Therefore, individual variations in scoring are unlikely to account for the frequency of delayed improvement found in our study. Additionally, because the number of patients with improved mRS scores at 1 year and 3 years was more than twice the number of patients with worse mRS scores at these same time points, interand intrarater variability is unlikely to account for our findings.…”
Section: Figmentioning
confidence: 70%
“…Imprecision in estimates of the treatment effect may have arisen from interobserver variability in determining the scores on the modified Rankin scale, 15,25 which was administered principally by telephone. Analysis of the net change in functional outcome was based on equal weights assigned to each score (0 through 6) on the modified Rankin scale, but patient and provider assessments can vary across health transitions, 26 and functional recovery can continue beyond 90 days.…”
Section: Low-dose Alteplase Bettermentioning
confidence: 99%
“…A primary limitation of SIS concerns feasibility and acceptability. Other commonly used scales in stroke are limited by imperfect reliability (mRS), floor and ceiling effects (BI), and poor validity for certain stroke syndromes (NIHSS) 21, 22, 23. The context of testing is also important.…”
Section: Discussionmentioning
confidence: 99%